Peran Majelis Ulama Indonesia (MUI) Dalam Meningkatkan Kualitas Dakwah Kota Pekanbaru, Riau - Annazri, Suci (FDIK IAIN Padangsidimpuan, 2021)
AbstractÂ The Indonesian Ulema Council has an important role in spreading its da'wah to Muslims. The da'wah was delivered aimed at minimizing the problems of the people of Pekanbaru City. With the recommendation to consume products that have halal certification and the implementation of premarital guidance which is categorized as Da'wah bil Hal. As for the problems that are troubling the community, such as products that are not in accordance with halal procedures both in health and Islamic teachings. Such as the case of foodstuffs originating from animals that are haram, the production process, and the delivery process. In addition, the implementation of premarital guidance is also needed, because considering the large number of people, especially prospective couples who have not interpreted the word marriage or having a family, so that wife and child abuse, as well as divorce rates are increasing.Â This research was conducted to determine the role of MUI as Warasatul anbiya' in spreading its da'wah to the people of the city of Pekanbaru. This research is a qualitative descriptive method, using primary data sources, the results of interviews with the Head of the MUI in Pekanbaru City, Riau while secondary data are taken from articles and other sources to support the relevance of this research.Â Keywords: Role of MUI, Da'wah, Pekanbaru City Society, Riau